1988
DOI: 10.1038/336388a0
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of self-reactive T cells before entry into the thymus medulla

Abstract: The thymus is important in the differentiation of bone marrow-derived precursor cells into functional T cells; humoral factors, as well as physical interactions with nurse cells, dendritic cells and epithelial cells, are thought to be instrumental in this process. Thymic lymphocytes mature during their migration from the cortical to the medullary region of the thymus, when they undergo phenotypic changes that include the acquisitions of T-cell antigen receptors, hormone receptors and differentiation antigens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 29 publications
2
78
0
Order By: Relevance
“…Although T cell clones express receptors for foreign antigen, positive selection of these clones by self-antigens during development in the thymus means that each clone has a measurable affinity for self-antigens. Although negative selection deletes strongly self-reactive T cells (1), this process is incomplete. T cells carrying receptors with intermediate and low affinity for self-antigen are routinely released into peripheral lymphoid tissues, where they may become activated, expand and possibly initiate autoimmune disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although T cell clones express receptors for foreign antigen, positive selection of these clones by self-antigens during development in the thymus means that each clone has a measurable affinity for self-antigens. Although negative selection deletes strongly self-reactive T cells (1), this process is incomplete. T cells carrying receptors with intermediate and low affinity for self-antigen are routinely released into peripheral lymphoid tissues, where they may become activated, expand and possibly initiate autoimmune disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cytokines like thymic stromal lymphopoietin (TSLP) produced by epithelial cells of thymic Hassall's corpuscles promote the conversion of CD4 + CD25-thymocytes into CD4 + CD25 + Foxp3 + T regulatory cells (Tregs) [49]. Dendritic cells in the thymus are also involved in the process of central tolerance [50].…”
Section: Dendritic Cells and Immune Tolerancementioning
confidence: 99%
“…In this regard, the pioneering work of Burnet and Medawar suggested that the definition of self versus nonself is arbitrary because foreign antigens presented during fetal life are thereafter considered self (1). Moreover, it is known that all T cells are self-referential in the sense that they are positively selected for survival on self-peptide(s) bound to MHC molecules during thymic positive selection (2) before thymic negative selection, in which thymocytes expressing TCR of high avidity to self-antigens are deleted (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that thymic negative selection, in which, high-avidity self-reactive thymocytes are deleted, eliminates the imminent danger of pathogenic autoimmunity in the periphery and is the major mechanism of central self-tolerance (3)(4)(5). However, while releasing the "innocent" selfreactive T cells with low avidity, thymic negative selection also allows a large fraction of self-reactive T cells of intermediate avidity to be released into the periphery under normal circumstances (10)(11)(12), and functional activation of this population of cells has the potential to elicit pathogenic autoimmunity (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%